2018
DOI: 10.1111/pbi.12951
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of OsTF1L, a rice HD‐Zip transcription factor, promotes lignin biosynthesis and stomatal closure that improves drought tolerance

Abstract: Drought stress seriously impacts on plant development and productivity. Improvement of drought tolerance without yield penalty is a great challenge in crop biotechnology. Here, we report that the rice (Oryza sativa) homeodomain-leucine zipper transcription factor gene, OsTF1L (Oryza sativa transcription factor 1-like), is a key regulator of drought tolerance mechanisms. Overexpression of the OsTF1L in rice significantly increased drought tolerance at the vegetative stages of growth and promoted both effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 80 publications
6
92
0
Order By: Relevance
“…Stomatal closure is the primary response to drought stress in most plants that curtail water loss from transpiration. Therefore, the stomatal aperture is a major factor that contributes to drought tolerance [68,69]. The present study demonstrated that plants pre-inoculated with B. amyloliquefaciens 54 had smaller stomatal aperture than did control plants ( Figure 5A,B).…”
Section: Discussionmentioning
confidence: 49%
“…Stomatal closure is the primary response to drought stress in most plants that curtail water loss from transpiration. Therefore, the stomatal aperture is a major factor that contributes to drought tolerance [68,69]. The present study demonstrated that plants pre-inoculated with B. amyloliquefaciens 54 had smaller stomatal aperture than did control plants ( Figure 5A,B).…”
Section: Discussionmentioning
confidence: 49%
“…Many studies have shown that transcription factors (TFs) are important regulators of drought stress signaling, and increasing their activity can provide plants with the ability to survive under drought conditions 1 . For example, the basic region/leucine zipper (bZIP) family has been characterized in a range of plant species, such as Arabidopsis thaliana 4,5 , rice (Oryza sativa) 6,7 , tomato (Solanum lycopersicum) 8 , maize (Zea mays) 9 , and grapevine (Vitis vinifera) 10,11 , and some of its members have been shown to enhance drought tolerance following overexpression in transgenic plants [5][6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al (2016) revealed that OsERF71 promoted lignin biosynthesis in rice by directly activating the expression of lignin biosynthesis genes such as CINNAMOYL-COENZYME A REDUCTASE 1 (OsCCR1), and root-specific lignification by OsERF71 promoted drought tolerance and increased grain yield up to 23-32% under drought conditions [100]. The role of lignin in rice stress tolerance is also supported by a recent study of OsTF1L, a rice HD-Zip transcription factor that regulates lignin biosynthesis [103].…”
Section: Root Development and Stress Tolerance In Ricementioning
confidence: 81%